Method for producing negative electrode material for lithium ion secondary battery, and method for producing lithium ion secondary battery

By using a mixture of water-based adhesives to mold, graphitize and crush the negative electrode material of lithium-ion secondary battery, the problems of low manufacturing efficiency and difficulty in crushing are solved, and efficient manufacturing and excellent lithium-ion secondary battery negative electrode material are achieved. battery performance.

CN119137768APending Publication Date: 2024-12-13RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095539.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lithium-ion secondary battery negative electrode materials have low manufacturing efficiency, poor manipulation of molded substances, and difficult to crush graphite, affecting battery performance.

Method used

Using a mixture containing a water-based adhesive, the negative electrode material of lithium-ion secondary battery is produced by molding, graphitization and crushing processes, and the strength and density of the molded product are improved by using water-soluble or water-absorbing polymer compounds in the water-based adhesive to reduce the strength and density of the molded product. The density of graphite is easy to crush.

Benefits of technology

The manufacturing efficiency and strength of the negative electrode material of lithium-ion secondary battery are improved, and the crushing of graphite is facilitated, the battery life is extended and the circulation characteristics are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109113180000241
    Figure BDA0005109113180000241
  • Figure BDA0005109113180000242
    Figure BDA0005109113180000242
Patent Text Reader

Abstract

Disclosed is a method for producing a negative electrode material for a lithium ion secondary battery. The present invention relates to a method for producing a graphitizable aggregate, comprising (a) a step for obtaining a mixture containing a graphitizable aggregate and a graphitizable binder, (b) a step for obtaining a molded product by molding the mixture, (c) a step for obtaining a graphitized product by graphitizing the molded product, and (d) a step for obtaining a pulverized product by pulverizing the graphitized product, the binder contains a water-based binder, and the water-based binder contains a water-soluble or water-absorbent polymer compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a negative electrode material for a lithium ion secondary battery and a method for producing a lithium ion secondary battery. Background Art

[0002] Compared with other secondary batteries such as nickel-cadmium batteries, nickel-metal hydride batteries, and lead-acid batteries, lithium-ion secondary batteries have higher energy density and are therefore widely used as power sources for portable electronic products such as laptop computers and mobile phones. Lithium-ion secondary batteries are expected to be used in relatively small electronic products as well as in electric vehicles and power sources for power storage.

[0003] As a material (negative electrode material) for the negative electrode of a lithium ion secondary battery, graphite is widely used. As a method for manufacturing a negative electrode material using graphite, for example, Patent Document 1 describes the following method: a mixture obtained by mixing a carbon material and a binder is crushed, the crushed product is molded using a mold, graphitized in this state, and the obtained graphitized product is further crushed.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2015 / 147012 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The demand for lithium-ion secondary batteries for electronic products, electric vehicles, power sources for power storage, and the like has increased, and along with this, there has been a demand for improved production efficiency of negative electrode materials for lithium-ion secondary batteries.

[0009] From the perspective of manufacturing efficiency of negative electrode materials for lithium ion secondary batteries, the present inventors have explored the following method: a mixture comprising a graphitizable aggregate and a graphitizable binder is molded, the molded product is graphitized to form a graphitized product, and the graphitized product is further crushed to obtain a crushed product, thereby manufacturing a negative electrode material for lithium ion secondary batteries.

[0010] In the method for manufacturing the negative electrode material for lithium ion secondary batteries, it is desirable to improve the strength of the molded product from the viewpoint of improving the operability of the molded product (e.g., operability in graphitization treatment, etc.). Furthermore, from the viewpoint of the ease of manufacturing the negative electrode material for lithium ion secondary batteries, it is desirable to be able to easily crush the graphitized product when it is made into a graphitized product.

[0011] In view of the above, an object of the present disclosure is to provide a method for producing a negative electrode material for a lithium ion secondary battery, which can produce a molded product having excellent strength and can easily pulverize a graphitized product, and a method for producing a lithium ion secondary battery including the negative electrode material production method.

[0012] Means for solving problems

[0013] Specific means for solving the above-mentioned problems include the following embodiments.

[0014] <1> A method for manufacturing a negative electrode material for a lithium ion secondary battery, comprising:

[0015] (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder,

[0016] (b) forming the mixture to obtain a formed product,

[0017] (c) a step of graphitizing the molded product to obtain a graphitized product, and

[0018] (d) a step of crushing the graphitized product to obtain a crushed product;

[0019] The binder includes a water-based binder containing a water-soluble or water-absorbing polymer compound.

[0020] <2> like <1> The method for producing a negative electrode material for a lithium ion secondary battery, wherein in the step of obtaining a molded product, the mixture is molded to obtain a material with a density greater than or equal to 1.25 g / cm 3 The molded object.

[0021] <3> A method for manufacturing a negative electrode material for a lithium ion secondary battery, comprising:

[0022] (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder,

[0023] (b) forming the mixture to obtain a density greater than or equal to 1.25 g / cm 3 The process of forming the product,

[0024] (c) graphitizing the molded product to obtain a density of less than or equal to 1.20 g / cm 3 The graphite process, and

[0025] (d) A step of pulverizing the graphitized product to obtain a pulverized product.

[0026] <4> A method for manufacturing a negative electrode material for a lithium ion secondary battery, comprising:

[0027] (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder,

[0028] (b) forming the mixture by extrusion molding to obtain a molded product,

[0029] (c) graphitizing the molded product to obtain a density of less than or equal to 1.50 g / cm 3 The graphite process, and

[0030] (d) A step of pulverizing the graphitized product to obtain a pulverized product.

[0031] <5> like <3> or <4> In the method for producing a negative electrode material for a lithium ion secondary battery, the binder comprises an aqueous binder, and the aqueous binder contains a water-soluble or water-absorbent polymer compound.

[0032] <6> like <1> , <2> and <5> The method for producing a negative electrode material for a lithium ion secondary battery according to any one of the preceding claims, wherein the water-soluble or water-absorbing polymer compound comprises at least one selected from the group consisting of starch, amylose, amylopectin, polyacrylic acid, carboxymethyl cellulose, polyvinyl alcohol and water-soluble protein.

[0033] <7> like <1> , <2> , <5> and <6> The method for producing a negative electrode material for a lithium ion secondary battery according to any one of the preceding claims, wherein the content of water in the mixture is 10% by mass to 50% by mass based on the total amount of the mixture.

[0034] <8> like <1> ~ <7> In any one of the above methods for producing a negative electrode material for a lithium ion secondary battery, the content of the binder in the mixture is 3% by mass to 30% by mass based on the total amount of the mixture.

[0035] <9> like <1> ~ <8> The method for producing a negative electrode material for a lithium ion secondary battery according to any one of the above aspects, wherein the aggregate comprises calcined coke.

[0036] <10> like <1> ~ <9> The method for producing a negative electrode material for a lithium ion secondary battery according to any one of the above aspects, wherein the aggregate contains green coke that has not been subjected to heat treatment.

[0037] <11> A method for manufacturing a lithium-ion secondary battery, comprising:

[0038] pass <1> ~ <10> The method for producing a negative electrode material for a lithium ion secondary battery according to any one of the preceding claims, comprising: a step of producing a negative electrode material for a lithium ion secondary battery, and

[0039] A step of producing a negative electrode using the negative electrode material for a lithium ion secondary battery.

[0040] Effects of the Invention

[0041] According to the present disclosure, it is possible to provide a method for producing a negative electrode material for a lithium ion secondary battery, which can produce a molded product having excellent strength and can easily pulverize a graphitized product, and a method for producing a lithium ion secondary battery including the negative electrode material production method. DETAILED DESCRIPTION

[0042] Hereinafter, the mode for implementing the present invention is described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, its constituent elements (including element steps, etc.) are not necessary except for the cases that are clearly considered to be necessary in principle, etc., except for the cases that are particularly clearly indicated. The numerical value and its range are also the same and do not limit the present invention.

[0043] In the present disclosure, the term "process" includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.

[0044] In the present disclosure, in a numerical range expressed using “to”, the numerical values ​​described before and after “to” are included as the minimum value and the maximum value, respectively.

[0045] In the numerical ranges recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiments.

[0046] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, the content or content of each component refers to the total content or content of the plurality of substances present in the composition unless otherwise specified.

[0047] In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition unless otherwise specified.

[0048] In the present disclosure, the word "layer" includes a case where the layer is formed in the entire region and a case where the layer is formed in only a part of the region when looking at the region where the layer exists.

[0049] <Method for producing negative electrode material for lithium ion secondary battery>

[0050] [First embodiment]

[0051] The first embodiment of the present disclosure involves a method for producing a negative electrode material for a lithium ion secondary battery (hereinafter also referred to as a negative electrode material), comprising: (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder, (b) a step of molding the mixture to obtain a molded product, (c) a step of graphitizing the molded product to obtain a graphitized product, and (d) a step of crushing the graphitized product to obtain a crushed product, wherein the binder comprises an aqueous binder, and the aqueous binder contains a water-soluble or water-absorbent polymer compound.

[0052] It should be noted that each step of the above method can be carried out continuously or discontinuously. Each step of the above method can be carried out in the same place or in different places.

[0053] In the manufacturing method of the present embodiment, an aqueous binder containing a water-soluble or water-absorbent polymer compound is used. As a result, the strength of the molded product is improved, and thus the operability in the subsequent graphitization treatment is also improved. When the strength of the molded product is improved, there is usually a tendency that the graphitized product after the graphitization treatment of the molded product is difficult to crush. However, in the manufacturing method of the present embodiment, by using the above-mentioned aqueous binder, the strength of the molded product can be improved, and the graphitized product can be easily crushed.

[0054] The reason why the graphite material can be easily crushed while improving the strength of the molded product in the production method of the present embodiment is presumed to be as follows. It should be noted that the present disclosure is not limited to the following presumption.

[0055] In the manufacturing method of the present embodiment, an aqueous binder containing a water-soluble or water-absorbent polymer compound is used, so that the aggregate is incorporated into the binder swollen by water. Thus, the surface of the graphitizable aggregate becomes slippery when the mixture is formed, the mixture is arranged, and the gap becomes less. As a result, there is a tendency that the density and strength of the molded object are improved. Furthermore, the gaps between the aggregates are filled with water that is not incorporated into the binder, thereby showing a liquid bridge, so that the strength of the molded object is improved.

[0056] In the manufacturing method of this embodiment, after the molded product is heat-treated by heating as needed, the molded product is graphitized to obtain a graphitized product. By using an aqueous binder, water evaporates during heat treatment, graphitization, etc. Therefore, the molded product before heat treatment, graphitization, etc. has a high density, but the density of the graphitized product after graphitization decreases. Therefore, the graphitized product can be easily crushed.

[0057] Furthermore, in the manufacturing method of the present embodiment, the graphite can be easily crushed, and as a result, it becomes easy to obtain a crushed product with a small specific surface area. By using the negative electrode material containing the crushed product with a small specific surface area for the production of a lithium-ion secondary battery, the contact area between the negative electrode material and the electrolyte can be reduced. As a result, the decomposition reaction of the electrolyte is suppressed, and the life of the battery can be extended. As a result, there is a tendency for the lithium-ion secondary battery to have excellent cycle characteristics.

[0058] In the past, when raw coke was used, there were problems such as difficulty in molding and low strength of the molded product, and it was necessary to improve the moldability and strength of the molded product by heat treating the raw coke. On the other hand, in the manufacturing method of the present embodiment, even when raw coke is used without heat treatment, a molded product with excellent moldability and high strength can be obtained. Therefore, as a graphitizable aggregate, a substance (calcined coke) obtained by heat treating raw coke can be used for the formation of a molded product, and raw coke that has not been heat treated can also be used for the formation of a molded product.

[0059] In the manufacturing method of this embodiment, since the strength of the molded product is excellent, it is not necessary to load the mixture into a graphitization crucible or the like when graphitizing. That is, it is not necessary to use a graphitization crucible or the like, and the molded product can be graphitized by simply placing it in a graphitization furnace. Therefore, compared with the case of using a graphitization crucible or the like, there is a tendency that the manufacturing efficiency of the negative electrode material for a lithium ion secondary battery is excellent.

[0060] Generally, by increasing the amount of graphitizable binder, the strength of the molded product can be improved. However, when the amount of graphitizable binder is excessive, the density of the graphitized product is high, and there is a tendency for the graphitized product to be difficult to crush, and the battery characteristics such as the initial charge and discharge efficiency of the negative electrode material are easily reduced. In this embodiment, even if the amount of graphitizable binder is not increased, the strength of the molded product can be improved, and the reduction of battery characteristics caused by excessive use of the binder can also be prevented. Furthermore, by reducing the amount of binder, it is also easy to coat the surface of the crushed product with hard carbon, and there is a tendency to also improve the input characteristics of the lithium ion secondary battery.

[0061] In step (a), a mixture comprising a graphitizable aggregate and a graphitizable binder is obtained. The graphitizable binder comprises an aqueous binder, and the aqueous binder contains a water-soluble or water-absorbent polymer compound. There is no particular limitation on the method for obtaining the mixture, and a kneader or the like can be used for the mixture. The mixing can be carried out at room temperature or by heating. When an aqueous binder is used, asphalt, tar, etc. can be omitted as the graphitizable binder, or the amount of asphalt, tar, etc. used can be reduced. Therefore, it is not necessary to mix at a temperature at which the graphitizable binder softens, and treatments such as heating can be omitted.

[0062] The time for mixing the graphitizable aggregate and the graphitizable binder by kneading is not particularly limited, and can be, for example, 10 seconds to 30 minutes, 30 seconds to 20 minutes, or 1 minute to 15 minutes. The longer the mixing time, the higher the density and strength of the molded product.

[0063] The graphitizable aggregate is not particularly limited as long as it is an aggregate that is graphitized by graphitization. Specifically, cokes such as liquid coke, needle coke, and mosaic coke can be cited. Among them, needle coke is preferably used from the viewpoint of being able to easily pulverize the graphitized product by suppressing the increase in the density of the manufactured graphitized product. The graphitizable aggregate is preferably in a particle form.

[0064] The graphitizable aggregate contained in the mixture may be only one kind or two or more kinds.

[0065] When coke is used as a graphitizable aggregate, the coke may include calcined coke from the viewpoint of improving the strength of the molded product. It should be noted that in the manufacturing method of the embodiment, since the molded product has excellent strength, unheat-treated raw coke may be used to form the molded product.

[0066] When the graphitizable aggregate is in the form of particles, the average particle size of the graphitizable aggregate is, for example, preferably 5 μm to 40 μm, more preferably 8 μm to 30 μm, and further preferably 8 μm to 25 μm. The average particle size is, for example, a volume average particle size (D50) measured by a laser diffraction scattering method described later. The volume average particle size (D50) is the particle size when the cumulative volume cumulative distribution curve is drawn from the smaller diameter side in the particle size distribution to reach 50%.

[0067] The standard deviation of the particle size distribution of the graphitizable aggregate is, for example, preferably less than or equal to 0.25, more preferably less than or equal to 0.20, further preferably less than or equal to 0.18, and particularly preferably less than or equal to 0.16. By making the standard deviation of the particle size distribution of the above-mentioned aggregate less than or equal to 0.20, the deviation of the particle size of the aggregate can be reduced, and the deviation of the particle size of the obtained crushed material can also be suppressed. By using the negative electrode material of the crushed material containing a small deviation in particle size for the production of a lithium-ion secondary battery, the resistance distribution in the negative electrode can be uniformized. As a result, there is a tendency for the rapid charging performance of lithium-ion secondary batteries to improve. Furthermore, by reducing the deviation in the particle size of the aggregate, even if the content or content of the graphitizable binder is reduced, the function as a binder can be appropriately ensured. The standard deviation of the particle size distribution is, for example, a value (volume basis) measured by the laser diffraction scattering method described later.

[0068] The lower limit of the standard deviation of the particle size distribution of the graphitizable aggregate is not particularly limited, and may be, for example, 0.05 or more, or 0.10 or more.

[0069] Examples of a method for adjusting the average particle size of the graphitizable aggregate and the standard deviation of the particle size distribution of the graphitizable aggregate to the above ranges include classification using a sieve, wind classification, wet classification, and the like.

[0070] The graphitizable binder is not particularly limited as long as it is a water-based binder containing a water-soluble or water-absorbent polymer compound and is graphitized by graphitization. As the water-based binder, a composition containing a water-soluble or water-absorbent polymer compound and water can be cited. The graphitizable binder may contain one water-soluble or water-absorbent polymer compound, or may contain two or more water-soluble or water-absorbent polymer compounds.

[0071] From the viewpoint of suppressing the rupture of the molded body, the adhesion of the water-based adhesive is preferably greater than or equal to 0.2N, and from the viewpoint of obtaining a molded body with better strength, it is preferably greater than or equal to 0.4N. The adhesion of the water-based adhesive is measured as follows. First, 25g of the adhesive and 100g of water are mixed, and a sample is prepared by mixing with a roller mixer for 1 hour. 20g to 30g of the sample is filled into a mold with a diameter of 20mm, and a small table tester EZ-S made by Shimadzu Corporation is used to press 10mm at a descending speed of 60mm / min, and then a tensile test is performed at an ascending speed of 600mm / min to obtain the adhesion. There is a tendency that the adhesion of the water-based adhesive increases when the concentration of the adhesive increases. By ensuring that the moisture content is below a certain level, the function of the adhesive can be fully exerted, and there is a tendency that the bonding force can be maintained.

[0072] The graphitizable binder may contain components other than the water-based binder, and may contain, for example, coal-based, petroleum-based, artificial asphalt and tar, thermoplastic resin, thermosetting resin and other binders.

[0073] The water-soluble or water-absorbing polymer compound is not particularly limited, and may include, for example, at least one selected from the group consisting of starch, amylose, amylopectin, polyacrylic acid, carboxymethyl cellulose, polyvinyl alcohol, and water-soluble proteins.

[0074] The content of the aqueous binder in the graphitizable binder is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, and further preferably 90 to 100% by mass, based on the total amount of the binder.

[0075] In the present disclosure, the water-based binder refers to a composition of water, a water-soluble or water-absorbing polymer compound that functions as a binder, and a water-soluble or water-absorbing monomer component that is contained as necessary.

[0076] From the viewpoint of moldability and strength of the molded product, the water content in the mixture is preferably 10 to 50% by mass, more preferably 12 to 40% by mass, and further preferably 15 to 35% by mass based on the total amount of the mixture.

[0077] From the viewpoint of moldability and strength of the molded product, the content of the water-soluble or water-absorbing polymer compound in the binder is preferably 10% to 70% by mass, more preferably 15% to 60% by mass, and further preferably 15% to 50% by mass relative to the total amount of the binder.

[0078] From the viewpoint of moldability and strength of the molded product, the content of the water-soluble or water-absorbing polymer compound in the mixture is preferably 3% to 30% by mass, more preferably 4% to 25% by mass, and further preferably 5% to 20% by mass relative to the total amount of the mixture.

[0079] From the viewpoint of moldability and strength of the molded product, the water content in the aqueous binder is preferably 30 to 90% by mass, more preferably 40 to 85% by mass, and even more preferably 50 to 85% by mass relative to the total amount of the binder.

[0080] The mixture may or may not contain components other than the graphitizable aggregate or the graphitizable binder (hereinafter also referred to as "other components"). Examples of other components include aromatic compounds, graphite, dispersants, and graphitization catalysts.

[0081] The aromatic compound is not particularly limited as long as it is a compound having an aromatic ring. The aromatic compound may be a compound having an aromatic ring and a molecular weight of 500 or less, or a compound having a molecular weight of 300 or less.

[0082] Examples of the aromatic compound include naphthalene, methylnaphthalene such as 1-methylnaphthalene and 2-methylnaphthalene, acenaphthene, biphenyl, fluorene, benzopyrene, benzanthracene, dibenzanthracene, dibenzofuran, quinoline, and isoquinoline.

[0083] The aromatic compound contained in the mixture may be only one kind or two or more kinds.

[0084] Among them, as the aromatic compound, methylnaphthalene and naphthalene are preferred from the viewpoint of moldability when forming a molded product.

[0085] When the mixture contains aromatic compounds, the amount thereof is not particularly limited. The content of the aromatic compounds in the mixture is preferably less than or equal to 1% by mass, more preferably less than or equal to 0.5% by mass, and further preferably 0% by mass, relative to the total amount of the mixture.

[0086] The mixture may contain graphite. Examples of graphite include natural graphite and artificial graphite. The graphite is preferably in the form of particles. The mixture may contain only one type of graphite or two or more types.

[0087] From the viewpoint of easily dispersing the components in the mixture in step (b), the mixture preferably contains a dispersant. By including a dispersant in the mixture, the deviation of the particle size of the pulverized product obtained by pulverizing the graphitized product can be suppressed, and it becomes easy to obtain a pulverized product with aligned particle sizes. As a result, there is a tendency for the rapid charging performance of the lithium ion secondary battery to be improved.

[0088] Furthermore, by including a dispersant in the mixture, the amount of the graphitizable binder can be suppressed, and improvement in battery characteristics such as the initial charge and discharge efficiency of the negative electrode material can be expected.

[0089] There is no particular restriction on the type of dispersant. Specifically, hydrocarbons such as liquid paraffin, paraffin, polyethylene wax, stearic acid, oleic acid, erucic acid, 12-hydroxystearic acid, and other fatty acids, zinc stearate, lead stearate, aluminum stearate, calcium stearate, magnesium stearate and other fatty acid metal salts, stearic acid amide, oleic acid amide, erucic acid amide, methylene bis stearic acid amide, ethylene bis stearic acid amide and other fatty acid amides, stearic acid monoglyceride, stearyl stearate, hardened oil and other fatty acid esters, stearyl alcohol and other higher alcohols, etc. Among them, fatty acids are preferred, and stearic acid is more preferred, from the aspects of not easily affecting the performance of the negative electrode material, being easy to handle because it is solid at room temperature, disappearing in the process until graphitization treatment, and being cheap.

[0090] When the mixture contains a dispersant, the amount thereof is not particularly limited. For example, the content of the dispersant relative to the entire mixture may be 0.1% to 20% by mass, 0.5% to 10% by mass, or 0.5% to 5% by mass.

[0091] From the viewpoint of promoting graphitization of the graphitizable aggregate or binder, the mixture preferably contains a graphitization catalyst. The type of graphitization catalyst is not particularly limited. Specifically, it can be exemplified by substances having a graphitization catalytic effect such as silicon, iron, nickel, titanium, boron, carbides of these substances, oxides of these substances, nitrides of these substances, and the like.

[0092] When the mixture contains a graphitization catalyst, the amount thereof is not particularly limited. For example, the content of the graphitization catalyst relative to the entire mixture may be 0.1% to 50% by mass, 0.5% to 40% by mass, or 0.5% to 30% by mass.

[0093] In step (b), the mixture obtained in step (a) is molded to obtain a molded product. Preferably, the molded product is molded into a predetermined shape by a uniaxial press or the like. By molding in this way, the amount of filling into the graphitization furnace can be increased when the mixture is graphitized to improve productivity, or the effect of the graphitization catalyst can be improved.

[0094] In step (b), there is no particular limitation on the method for molding the mixture. For example, there can be mentioned: a molding method in which the mixture is placed in a container such as a mold and pressurized in a uniaxial direction; a vibration molding method in which the mixture is placed in a container such as a mold, a weight is placed on the upper surface, and a metal frame is vibrated and impacted to perform molding; an extrusion molding method in which the mixture is extruded from a nozzle or the like using a transverse press to perform molding, etc.

[0095] In step (b), the mixture is preferably formed by extrusion molding to obtain a molded product. By utilizing extrusion molding to mold the mixture, the manufacturing efficiency of the molded product is excellent, and the density of the molded product is improved and the operability is improved. Usually when extrusion molding is performed, the density of the molded product becomes higher, so the density of the graphitized product also becomes higher, and the problem of not being able to easily crush the graphitized product is easily generated. However, in the present embodiment, the water will volatilize when heat treatment, graphitization, etc. are performed, so even in the case of extrusion molding, the density of the graphitized product will also be reduced, and the graphitized product can be easily crushed.

[0096] In step (b), the density of the obtained molded product is not particularly limited, and may be, for example, greater than or equal to 0.90 g / cm 3 , can be greater than or equal to 0.95g / cm 3 , can be greater than or equal to 1.00g / cm 3 , can be greater than or equal to 1.25g / cm 3 , can be greater than or equal to 1.30g / cm 3 , can also exceed 1.30g / cm 3 The density of the obtained molded product can be less than or equal to 1.70 g / cm 3 , can be less than or equal to 1.60g / cm 3 , can also be less than or equal to 1.55g / cm 3 .

[0097] In the manufacturing method of this embodiment, since a water-based binder is used, even when the density of the molded product is low (for example, less than 1.25 g / cm 3 The strength of the molded product also tends to be improved in the case of a high density (for example, greater than or equal to 1.25 g / cm). By using an aqueous binder, water evaporates during heat treatment, graphitization, etc., so there is a tendency that the strength of the molded product will be improved even in the case of a high density (for example, greater than or equal to 1.25 g / cm 3 ), the density of the graphite tends to decrease. As a result, there is a tendency that the graphite can be easily crushed and a crushed material with a small specific surface area can be obtained. By using a negative electrode material containing a crushed material with a small specific surface area for the production of a lithium-ion secondary battery, the contact area between the negative electrode material and the electrolyte can be reduced. Based on the above, there is a tendency that the decomposition reaction of the electrolyte can be suppressed to extend the life of the battery, and a lithium-ion secondary battery with excellent cycle characteristics can be manufactured.

[0098] The molded product obtained in step (b) is preferably subjected to heat treatment before graphitizing the molded product in step (c). By performing heat treatment, organic components contained in the mixture that do not contribute to graphitization are removed, and there is a tendency to suppress gas generation during graphitization.

[0099] The temperature of the heat treatment is not particularly limited, but is preferably a temperature lower than the temperature of the heat treatment during graphitization in step (c). For example, the heat treatment can be performed in the range of 500°C to 1000°C.

[0100] In step (c), the molded product obtained in step (b) is graphitized. The method of graphitizing the molded product is not particularly limited as long as the conditions under which the graphitizable components contained in the mixture can be graphitized. For example, a method of heat treating the mixture in an atmosphere that is difficult to oxidize can be cited. The atmosphere that is difficult to oxidize the mixture is not particularly limited, and an inactive atmosphere such as nitrogen and argon, a vacuum, etc. can be cited.

[0101] The temperature of the heat treatment for graphitization may be, for example, greater than or equal to 1500°C, greater than or equal to 2000°C, greater than or equal to 2500°C, or greater than or equal to 2800°C. There is no particular upper limit to the temperature of the heat treatment, and for example, it may be less than or equal to 3200°C. When the temperature of the heat treatment is greater than or equal to 1500°C, there is a tendency for the crystallization to change and graphitization to proceed easily. When the temperature of the heat treatment is greater than or equal to 2000°C, there is a tendency for the development of graphite crystallization to become better. On the other hand, when the temperature of the heat treatment for graphitization is less than or equal to 3200°C, there is a tendency for sublimation of part of the graphite to be suppressed.

[0102] In step (c), the density of the graphite obtained is not particularly limited, but may be, for example, 0.80 g / cm or more from the viewpoint of the handleability of the graphite. 3 , can be greater than or equal to 0.85g / cm 3 , or greater than or equal to 0.90 g / cm 3 From the perspective of the ease of pulverization of the graphite, the density of the obtained graphite can be less than or equal to 1.50 g / cm 3 , can be less than or equal to 1.30g / cm 3 , can be less than or equal to 1.20g / cm 3 , can be less than or equal to 1.15g / cm 3 , can be less than or equal to 1.12g / cm 3 , or less than or equal to 1.10 g / cm 3 .

[0103] In step (d), the graphitized product obtained in step (c) is pulverized to obtain a pulverized product. The pulverization method is not particularly limited, and it can be carried out by a known method using a jet mill, a vibration mill, a pin mill, a hammer mill, etc. The pulverized product can be adjusted in particle size to a desired size. The method for adjusting the particle size is not particularly limited, and examples thereof include a method using the above-mentioned pulverization device, a method using a sieve, and the like.

[0104] If necessary, the pulverized product obtained in step (d) may be subjected to steps such as (e) disposing low-crystalline carbon on at least a portion of the surface of the pulverized product, (f) mixing the pulverized product with other negative electrode active materials, and the like.

[0105] As a method for configuring low-crystalline carbon on at least a portion of the surface of the pulverized product in step (e), for example, a method of mixing a substance (resin, etc.) that can become low-crystalline carbon by heat treatment with the pulverized product and heat treating the mixture can be cited. If low-crystalline carbon is configured on at least a portion of the surface of the pulverized product, the input-output characteristics such as the rapid charge and discharge characteristics of a lithium-ion secondary battery using the pulverized product as a negative electrode material may be improved.

[0106] There is no particular limitation on the method of mixing the pulverized material with other negative electrode active materials in step (f). By mixing the pulverized material with other negative electrode active materials, the desired properties of the lithium ion secondary battery can sometimes be improved compared to the case where only the pulverized material is used as the negative electrode active material. As other negative electrode active materials, graphite particles such as natural graphite and artificial graphite, particles containing elements capable of absorbing and releasing lithium ions, etc. can be cited, but are not limited to these. As elements capable of absorbing and releasing lithium ions, there is no particular limitation, for example, Si, Sn, Ge, In, etc. can be cited.

[0107] The pulverized material obtained in step (f) may include particles in which a plurality of flat graphite particles are aggregated or combined, or may include particles in which a plurality of flat graphite particles are aggregated or combined in a manner in which the main surfaces of the graphite particles are not parallel to each other (hereinafter also referred to as graphite secondary particles).

[0108] If the pulverized product is in the form of graphite secondary particles, when pressing is performed to increase the density of the negative electrode, the negative electrode material particles are suppressed from being oriented toward the current collector, and there is a tendency that a sufficient path for lithium ions to enter and exit the negative electrode material can be ensured.

[0109] Furthermore, by including particles in a state where a plurality of flat graphite particles are aggregated or combined, the effect of the pressure applied during pressing on the individual graphite particles is reduced due to the gaps between the plurality of flat graphite particles, and there is a tendency that the destruction of the graphite particles, the generation of cracks, etc. are suppressed.

[0110] In the present disclosure, "flat graphite particles" refer to non-spherical graphite particles having anisotropic shapes. Examples of flat graphite particles include graphite particles having shapes such as scales, flakes, and partially blocky shapes.

[0111] When the length of the long axis direction of the flat graphite particles is set to A and the length of the short axis direction is set to B, the aspect ratio represented by A / B is preferably 1.2 to 20, and more preferably 1.3 to 10. When the aspect ratio is greater than or equal to 1.2, the contact area between the particles increases, and there is a tendency for the conductivity to be further improved. When the aspect ratio is less than or equal to 20, there is a tendency for the input and output characteristics such as the rapid charge and discharge characteristics of the lithium ion secondary battery to be further improved.

[0112] The aspect ratio is obtained by observing graphite particles under a microscope, randomly selecting 100 graphite particles and measuring their respective A / B, and taking the arithmetic mean of their measured values. In the observation of the aspect ratio, the length A in the major axis direction and the length B in the minor axis direction are measured as follows. That is, in the projected image of the graphite particles observed using a microscope, the tangent a1 and the tangent a2 with the largest distance between the two parallel tangents circumscribed to the periphery of the graphite particles are selected, and the distance between the tangent a1 and the tangent a2 is used as the length A in the major axis direction. The tangent b1 and the tangent b2 with the smallest distance between the two parallel tangents circumscribed to the periphery of the graphite particles are selected, and the distance between the tangent b1 and the tangent b2 is used as the length B in the minor axis direction.

[0113] In the present disclosure, the "non-parallel principal surface" of the graphite secondary particles refers to that the surface (principal surface) with the largest cross-sectional area of ​​a plurality of flat graphite particles is not aligned in a certain direction. Whether the principal surfaces of a plurality of flat graphite particles are non-parallel to each other can be confirmed by microscopic observation. By a plurality of flat graphite particles being assembled or combined in a state where the principal surfaces are non-parallel to each other, the orientation of the principal surface of the flat graphite particles in the negative electrode can be suppressed, the expansion of the negative electrode accompanying charging can be suppressed, and there is a tendency for the cycle characteristics of the lithium-ion secondary battery to be further improved.

[0114] In addition, the graphite secondary particles may partially include a structure in which a plurality of flat graphite particles are aggregated or bonded so that their main surfaces are parallel to each other.

[0115] In the present disclosure, the "aggregated or bonded state" of a plurality of flat graphite particles refers to a state in which two or more flat graphite particles are aggregated or bonded. "Bonding" refers to a state in which particles are chemically bonded to each other directly or via a carbon substance. "Aggregation" refers to a state in which particles are not chemically bonded to each other but maintain a shape as an aggregate due to their shape, etc. The flat graphite particles may also be aggregated or bonded via a carbon substance. As the carbon substance, for example, a graphitized product of a graphitizable binder may be cited. From the viewpoint of mechanical strength, it is preferred that two or more flat graphite particles are bonded via a carbon substance. Whether the flat graphite particles are aggregated or bonded can be confirmed, for example, by observation using a scanning electron microscope.

[0116] From the viewpoint of easy aggregation or combination, the average particle size of the flat graphite particles is, for example, preferably 1 μm to 50 μm, more preferably 1 μm to 25 μm, and further preferably 1 μm to 15 μm. As a method for measuring the average particle size of the flat graphite particles, a method for measuring using a scanning electron microscope can be cited, and the average particle size of the flat graphite particles is, for example, the arithmetic mean of the particle sizes of 100 flat graphite particles.

[0117] Flat graphite particles and raw materials thereof are not particularly limited, and can include artificial graphite, scaly natural graphite, scaly natural graphite, coke, resin, tar, pitch, etc. Among them, the graphite obtained by artificial graphite, natural graphite or coke has high crystallinity and becomes soft particles, so there is a tendency that the high density of the negative electrode becomes easy.

[0118] The negative electrode material may include spherical graphite particles. When the negative electrode material includes spherical graphite particles, the spherical graphite particles themselves have a high density, so there is a tendency that the pressing pressure required to obtain a desired electrode density can be reduced.

[0119] As spherical graphite particles, spherical artificial graphite, spherical natural graphite, etc. can be cited. From the viewpoint of high density of the negative electrode, the spherical graphite particles are preferably high-density graphite particles. Specifically, it is preferred to implement a particle spheroidization process to achieve high tap density spherical natural graphite. Furthermore, the negative electrode material layer containing spherical natural graphite has excellent peel strength, and there is a tendency that it is not easy to peel off from the collector even if it is strongly pressed.

[0120] When the negative electrode material includes spherical graphite particles, the flat graphite particles and spherical graphite particles mentioned above may be included. When the negative electrode material includes the flat graphite particles and spherical graphite particles mentioned above, the ratio of the two is not particularly limited and can be set according to the desired electrode density, the pressure conditions during pressing, the desired battery characteristics, etc.

[0121] In the case where the negative electrode material includes flat graphite particles and spherical graphite particles, there can be mentioned a state where flat graphite particles are mixed with spherical graphite particles, a state where flat graphite particles are combined with spherical graphite particles (hereinafter also referred to as composite particles), etc. As composite particles, for example, there can be mentioned particles in a state where flat graphite particles and spherical graphite particles are combined via carbides of organic matter.

[0122] The composite particles can be produced, for example, by using a mixture containing flat graphite particles or a raw material thereof and spherical graphite particles as the mixture in the step (a).

[0123] The average particle size of the negative electrode material manufactured by the above method is not particularly limited. For example, it is preferably 5 μm to 40 μm, more preferably 10 μm to 30 μm, and further preferably 10 μm to 25 μm. The average particle size can be measured, for example, by a scanning electron microscope in the same manner as the average particle size of the flat graphite particles, or can be a volume average particle size (D50) measured by a laser diffraction scattering method.

[0124] As a method for measuring the average particle size when using a negative electrode material to manufacture an electrode (negative electrode), it can be cited as follows: making a sample electrode, burying the electrode in epoxy resin, mirror polishing, and observing the electrode cross section with a scanning electron microscope (e.g., KEYENCE Co., Ltd., "VE-7800"); using an ion milling device (e.g., Hitachi High-Tech Co., Ltd., "E-3500") to make an electrode cross section, and measuring it with a scanning electron microscope (e.g., KEYENCE Co., Ltd., "VE-7800"), etc. The average particle size at this time is the median of 100 particle sizes arbitrarily selected from the observed particles.

[0125] The above-mentioned sample electrode can be prepared, for example, as follows: a mixture of 98 parts by mass of negative electrode material, 1 part by mass of styrene butadiene resin as a binder and 1 part by mass of carboxymethyl cellulose as a thickener is used as a solid component, water is added to prepare a dispersion, the above-mentioned dispersion is applied on a copper foil with a thickness of 10 μm in a manner to a thickness of about 70 μm (when applied), and then dried at 105°C for 1 hour.

[0126] The orientation of the negative electrode material when it is made into a negative electrode (when the negative electrode is produced with a pressing step, it is the pressed negative electrode) may be less than or equal to 40, less than or equal to 20, or less than or equal to 15. The above orientation may be greater than or equal to 10.

[0127] The orientation of the negative electrode material is an index indicating the degree of orientation of the particles of the negative electrode material contained in the negative electrode. Low orientation means that the particles of the negative electrode material are oriented in random directions. That is, it means that the graphite particles are suppressed from being oriented along the surface of the collector due to the pressure during pressing.

[0128] In the present disclosure, the orientation of the negative electrode is determined by measuring the surface of the sample electrode using an X-ray diffraction device using CuKα rays as an X-ray source. Specifically, the X-ray diffraction pattern of the surface of the sample electrode is measured, and the orientation is determined by the following formula (1) based on the intensity of the carbon (004) plane diffraction peak detected near the diffraction angle 2θ = 53° to 56° and the carbon (110) plane diffraction peak detected near the diffraction angle 2θ = 70° to 80°.

[0129] (004) plane diffraction peak intensity / (110) plane diffraction peak intensity...Formula (1)

[0130] From the viewpoint of cycle characteristics and storage characteristics, the specific surface area of ​​the negative electrode material is preferably less than or equal to 3.0 m 2 / g, more preferably less than or equal to 2.8m 2 / g, more preferably 0.5m 2 / g~2.5m 2 / g, particularly preferably 0.7m 2 / g~2.0m 2 / g.

[0131] The specific surface area of ​​the negative electrode material can be calculated by using a specific surface area / pore distribution measuring device (such as FlowSorbIII2310, Shimadzu Corporation) and a mixed gas of nitrogen and helium (nitrogen:helium = 3:7) to measure nitrogen adsorption at liquid nitrogen temperature (77K) by a one-point method at a relative pressure of 0.3, and then calculating the specific surface area by the BET method.

[0132] [Second embodiment]

[0133] The method for producing a negative electrode material according to a second embodiment of the present disclosure comprises: (a) obtaining a mixture including a graphitizable aggregate and a graphitizable binder, and (b) molding the mixture to obtain a graphitizable aggregate having a density of 1.25 g / cm or more. 3 (c) graphitizing the molded product to obtain a density of less than or equal to 1.20 g / cm 3 (d) the step of pulverizing the graphite to obtain a pulverized product.

[0134] In the present disclosure, the necessary configurations and preferred configurations in each embodiment may be appropriately combined. The preferred conditions of steps (b) and (c) other than the density of the molded product and the density of the graphitized product are the same as the preferred conditions of steps (b) and (c) in the first embodiment described above.

[0135] In the production method of this embodiment, the density of the molded product obtained in step (b) is set to be greater than or equal to 1.25 g / cm 3 , thereby improving the strength of the molded product. Therefore, the operability in the subsequent graphitization treatment is also improved. By making the density of the graphitized product obtained in step (c) less than or equal to 1.20 g / cm 3 , so that the graphite can be easily crushed.

[0136] Furthermore, in the manufacturing method of the present embodiment, the graphitized material can be easily crushed, and as a result, a crushed material with a small specific surface area can be easily obtained. By using the negative electrode material containing the crushed material with a small specific surface area for the production of a lithium-ion secondary battery, the contact area between the negative electrode material and the electrolyte can be reduced. As a result, the decomposition reaction of the electrolyte is suppressed and the life of the battery can be extended. As a result, there is a tendency that the cycle characteristics of the lithium-ion secondary battery are excellent.

[0137] In the manufacturing method of this embodiment, in step (b), the method for molding the mixture is not particularly limited. For example, the above-mentioned molding method, vibration molding method, extrusion molding method, etc. can be cited. From the viewpoint of reducing the density of the graphitized product, molding method or vibration molding method is preferred.

[0138] In the manufacturing method of this embodiment, from the viewpoint of suitably reducing the density of the graphitized product obtained in step (c), the graphitizable binder may include an aqueous binder containing a water-soluble or water-absorbent polymer compound. The preferred embodiment of the aqueous binder is the same as that of the first embodiment.

[0139] In step (b), the density of the obtained molded product is greater than or equal to 1.25 g / cm 3 , can be greater than or equal to 1.30g / cm3 , can also exceed 1.30g / cm 3 The density of the obtained molded product can be less than or equal to 1.70 g / cm 3 , can be less than or equal to 1.60g / cm 3 , or less than or equal to 1.55 g / cm 3 .

[0140] In step (c), the density of the obtained graphite is less than or equal to 1.20 g / cm 3 , can be less than or equal to 1.12g / cm 3 , or less than or equal to 1.10 g / cm 3 The density of the obtained graphite can be greater than or equal to 0.80 g / cm 3 , can be greater than or equal to 0.85g / cm 3 , or greater than or equal to 0.90 g / cm 3 .

[0141] [Third Embodiment]

[0142] The method for producing a negative electrode material according to the third embodiment of the present disclosure comprises: (a) obtaining a mixture containing a graphitizable aggregate and a graphitizable binder, (b) forming the mixture by extrusion molding to obtain a molded product, and (c) graphitizing the molded product to obtain a graphitized product having a density of less than or equal to 1.50 g / cm 3 (d) the step of pulverizing the graphite to obtain a pulverized product.

[0143] In the present disclosure, the necessary configurations and preferred configurations in each embodiment may be appropriately combined. The preferred conditions of steps (b) and (c) other than the molding method of the molded product and the density of the graphitized product are the same as those of steps (b) and (c) in the first embodiment described above.

[0144] In the manufacturing method of this embodiment, the strength of the molded product is improved by obtaining the molded product by extrusion molding in step (b). Therefore, the operability in the subsequent graphitization treatment is also improved. By making the density of the graphitized product obtained in step (c) less than or equal to 1.50 g / cm 3 , so that the graphite can be crushed relatively easily.

[0145] In the manufacturing method of this embodiment, from the viewpoint of suitably reducing the density of the graphitized product obtained in step (c), the graphitizable binder may include an aqueous binder containing a water-soluble or water-absorbent polymer compound. The preferred embodiment of the aqueous binder is the same as that of the first embodiment.

[0146] In step (b), the density of the obtained molded product may be greater than or equal to 1.25 g / cm 3 , can be greater than or equal to 1.30g / cm 3 , can also exceed 1.30g / cm 3 The density of the obtained molded product can be less than or equal to 1.70 g / cm 3 , can be less than or equal to 1.60g / cm 3 , or less than or equal to 1.55 g / cm 3 .

[0147] In step (c), the density of the obtained graphite is less than or equal to 1.50 g / cm 3 , can be less than or equal to 1.30g / cm 3 , can be less than or equal to 1.20g / cm 3 , can be less than or equal to 1.15g / cm 3 , can be less than or equal to 1.12g / cm 3 , or less than or equal to 1.10 g / cm 3 The density of the obtained graphite can be greater than or equal to 0.80 g / cm 3 , can be greater than or equal to 0.85g / cm 3 , or greater than or equal to 0.90 g / cm 3 .

[0148] In the manufacturing method of this embodiment, since the strength of the molded product is excellent, the green coke that has not been heat-treated can be used to form the molded product. Furthermore, by using the green coke that has not been heat-treated, the density of the graphitized product obtained in step (c) can be appropriately reduced, and the graphitized product can be crushed more easily.

[0149] <Method for producing lithium-ion secondary battery>

[0150] The method for producing a lithium ion secondary battery disclosed herein comprises a step of producing a negative electrode material by the method for producing a negative electrode material described above, and a step of producing a negative electrode using the negative electrode material.

[0151] The method of making a negative electrode using a negative electrode material is not particularly limited. For example, a method of forming a negative electrode material layer on a current collector using a composition containing a negative electrode material, a binder, and a solvent, and performing heat treatment, pressing treatment, etc. as needed can be mentioned.

[0152] The adhesive contained in the composition is not particularly limited. Examples include styrene-butadiene rubber, polymer compounds with ethylenically unsaturated carboxylic acid esters (methyl (meth) acrylate, ethyl (meth) acrylate, butyl (meth) acrylate, hydroxyethyl (meth) acrylate, etc.) as polymerization components, polymer compounds with ethylenically unsaturated carboxylic acids (acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, etc.) as polymerization components, polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, and polymer compounds such as polyamide-imide. In the present disclosure, (meth) acrylate refers to either or both of methacrylate and acrylate.

[0153] The solvent contained in the composition is not particularly limited, and specifically, organic solvents such as N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and γ-butyrolactone, and water can be used.

[0154] The composition may contain a thickener for adjusting the viscosity as required. Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid and salts thereof, oxidized starch, phosphorylated starch, casein, and the like.

[0155] The composition may contain a conductive auxiliary agent as required. Examples of the conductive auxiliary agent include carbon black, graphite, acetylene black, conductive oxides, and conductive nitrides.

[0156] The material and shape of the current collector used in the production of the negative electrode are not particularly limited. For example, materials such as strip foil, strip perforated foil, strip net made of metals or alloys such as aluminum, copper, nickel, titanium, stainless steel can be used. Porous materials such as porous metal (foamed metal) and carbon paper can also be used.

[0157] The method of using the composition to form a negative electrode material layer on a current collector is not particularly limited, and can be carried out by known methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, scraper method, gravure coating, screen printing, etc. In the case of integrating the above-mentioned negative electrode material layer with the current collector, it can be carried out by known methods such as roller, pressing, combinations thereof, etc.

[0158] After the negative electrode material layer is formed on the current collector, heat treatment (drying) can be performed. By performing heat treatment, the solvent contained in the negative electrode material layer is removed, and the high strength brought by the solidification of the binder is promoted, which can improve the adhesion between particles and between particles and the current collector. In order to prevent oxidation of the current collector during treatment, the heat treatment can be carried out in an inactive atmosphere such as helium, argon, nitrogen or a vacuum atmosphere.

[0159] After the negative electrode material layer is formed on the current collector, a pressing process may be performed. By performing the pressing process, the electrode density of the negative electrode can be adjusted. The electrode density of the negative electrode is not particularly limited and may be 1.5 g / cm 3 ~1.9g / cm 3 , can also be 1.6g / cm 3 ~1.8g / cm 3 The higher the electrode density, the higher the volume capacity of the negative electrode, the better the adhesion of the negative electrode material layer to the current collector, and the tendency for the cycle characteristics to improve. The pressing treatment is preferably performed before the heat treatment.

[0160] The lithium ion secondary battery manufactured by the above method may include a negative electrode, a positive electrode and an electrolyte manufactured by the above method. For example, the lithium ion secondary battery may be configured such that the negative electrode and the positive electrode are arranged to face each other with a separator interposed therebetween and an electrolyte solution containing an electrolyte is injected.

[0161] The positive electrode can be prepared by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. As the current collector, a strip-shaped foil, a strip-shaped perforated foil, a strip-shaped mesh, etc. made of a metal or alloy such as aluminum, titanium, stainless steel, etc. can be used.

[0162] There is no particular limitation on the positive electrode material contained in the positive electrode layer. For example, metal compounds, metal oxides, metal sulfides and conductive polymer materials that can be doped or embedded with lithium ions can be cited. Furthermore, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2) and their composite oxides (LiCoO2) can be used alone or in combination. x Ni y Mn z O2, x+y+z=1, 0<x, 0<y; LiNi 2-x Mn x O4, 0<x≤2), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene and other conductive polymers, porous carbon, etc. Among them, lithium nickel oxide (LiNiO2) and its composite oxide (LiCo x Ni y Mn z O2, x+y+z=1, 0<x, 0<y; LiNi 2- x Mn x O4, 0<x≤2) is suitable as a positive electrode material due to its high capacity.

[0163] Examples of the separator include nonwoven fabrics, fabrics, microporous films, and combinations thereof, which are mainly composed of polyolefins such as polyethylene and polypropylene. In addition, when the lithium ion secondary battery has a structure in which the positive electrode and the negative electrode are not in contact, a separator is not required.

[0164] As the electrolyte, a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3 dissolved in ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3- The so-called organic electrolyte obtained in a non-aqueous solvent of a monomer or a mixture of more than two components such as oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, etc. Among them, the electrolyte containing fluoroethylene carbonate has a tendency to form a stable SEI (solid electrolyte interface) on the surface of the negative electrode material, and the cycle characteristics are significantly improved, so it is preferred.

[0165] The form of the lithium ion secondary battery is not particularly limited, and examples thereof include paper batteries, button batteries, coin batteries, laminated batteries, cylindrical batteries, square batteries, etc. The negative electrode material for lithium ion secondary batteries can be applied to all kinds of electrochemical devices such as hybrid capacitors that use the insertion and extraction of lithium ions as a charging and discharging mechanism, in addition to lithium ion secondary batteries.

[0166] Example

[0167] Hereinafter, the above-mentioned embodiment will be described in more detail based on examples, but the above-mentioned embodiment is not limited to the following examples.

[0168] [Example 1]

[0169] (Formation of Molded Article)

[0170] As aggregate, green needle coke with an average particle size of 11 μm and a standard deviation of the particle size distribution of 0.25 without heat treatment was used, and the materials shown below were used as raw materials. The average particle size of the aggregate and the negative electrode material and the standard deviation of the particle size distribution of the aggregate were measured separately using a particle size distribution measuring device (SALD-3000, Shimadzu Corporation) using a laser diffraction scattering method. The standard deviation of the particle size distribution of the aggregate is a standard deviation defined on a logarithmic scale. The raw materials shown below were mixed without heating in the mixing ratios and conditions shown in Table 1 to prepare a mixture. Next, the obtained mixture was molded by a uniaxial press at room temperature to obtain a molded product of 10 mm×10 mm×50 mm.

[0171] Aggregate: Green needle coke with an average particle size of 11 μm and a standard deviation of particle size distribution of 0.25

[0172] ·Binder: Starch (10 parts by mass relative to 100 parts by mass of coke)

[0173] Water (33.2 parts by mass relative to 100 parts by mass of needle coke)

[0174] Next, the obtained molded product was heat treated at 800°C to 850°C for 8 hours in a nitrogen atmosphere to obtain a sintered product. Then, the obtained sintered product was graphitized at 2600°C to 3100°C for 30 hours to obtain a graphitized product. The obtained graphitized product was pulverized to obtain the graphite powder (negative electrode material for lithium ion secondary battery) of Example 1.

[0175] The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 1 respectively.

[0176] (Evaluation of bending test force)

[0177] The bending test force (N) of the molded product was measured as follows.

[0178] Specifically, the mixture of the composition shown in Table 1 was molded at room temperature to obtain a molded product of 10 mm×10 mm×50 mm. The density (g / cm 3 ) are shown in Table 1. Using the produced molded product and Autograph manufactured by Shimadzu Corporation, a three-point bending test was performed at a test speed of 10 mm / min and a support distance of 7 mm to measure the bending test force (N) required for destruction.

[0179] The results are shown in Table 1.

[0180] (Evaluation of Formability)

[0181] Three molded products were prepared in the same manner as in Example 1. The number of molded products that had defects of 1 mm or more during transportation was evaluated. When the number was 0, it means that none of the molded products prepared had the above-mentioned defects, and when the number was 3, it means that all the molded products prepared had the above-mentioned defects.

[0182] The results are shown in Table 1.

[0183] (Evaluation of large-scale moldability)

[0184] The obtained mixture was molded at room temperature to obtain a large-sized molded product of 150 mm × 300 mm × 100 mm. The obtained large-sized molded product was evaluated as being capable of large-sized molding when it could be lifted up with both hands without generating large cracks, large defects, etc., and was evaluated as being uncapable of large-sized molding when large cracks, large defects, etc., etc., were generated when the molded product was to be lifted up with both hands, or when the molded product could not be lifted up with both hands.

[0185] (Calculation of residual carbon rate)

[0186] The residual carbon rate was calculated based on the following formula: When starch was used as the binder, the carbon mass derived from the binder was set to 20% by mass of the input amount, and when tar pitch was used as the binder, the carbon mass derived from the binder was set to 50% by mass of the input amount.

[0187] Residual carbon rate (%) = [Carbon mass derived from binder / (Carbon mass derived from binder + Carbon mass derived from coke)] × 100

[0188] [Examples 2 to 8]

[0189] (Formation of Molded Article)

[0190] In Examples 2 to 8, calcined needle coke was used, which was produced by heat treating the raw needle coke used in Example 1 at 800°C to 850°C for 8 hours in a nitrogen atmosphere. Furthermore, the materials shown below were used as raw materials. The raw materials shown below were mixed without heating in the proportions and conditions shown in Table 1 to prepare a mixture. Next, using the obtained mixture, the same operation as in Example 1 was performed to obtain graphite powder (negative electrode material for lithium ion secondary batteries) of Examples 2 to 8. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 1 respectively.

[0191] Aggregate: Needle coke with an average particle size of 10 μm and a standard deviation of particle size distribution of 0.24

[0192] ·Binder: Starch (compounding amount shown in Table 1)

[0193] · Water (compound amount shown in Table 1)

[0194] [Example 9]

[0195] The same operation as in Example 1 was carried out except that the amount of water in Example 1 was changed to the amount shown in Table 1 to obtain the graphite powder (negative electrode material for lithium ion secondary battery) of Example 9. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 1 respectively.

[0196] [Examples 10 and 11]

[0197] The same operation as in Example 1 was performed except that the amount of water in Example 1 was changed to the amount shown in Table 1, the kneading time was changed to the time shown in Table 1, and the molding method was changed to extrusion molding to obtain graphite powders (negative electrode materials for lithium ion secondary batteries) of Examples 10 and 11. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 1 respectively.

[0198] The molded products obtained in Examples 2 to 11 were evaluated in the same manner as in Example 1. The results are shown in Table 1. "-" in the table means that there is no data.

[0199] [Comparative Example 1]

[0200] (Formation of Molded Article)

[0201] As an aggregate, green needle coke with an average particle size of 11 μm and a standard deviation of particle size distribution of 0.25 without heat treatment was used, and the materials shown below were used as raw materials. The raw materials shown below were heated and mixed at 140°C in the proportions and conditions shown in Table 2 to prepare a mixture. Then, using the obtained mixture, the same operation as in Example 1 was performed to obtain the graphite powder (negative electrode material for lithium-ion secondary batteries) of Comparative Example 1. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 2 respectively.

[0202] Aggregate: Green needle coke with an average particle size of 11 μm and a standard deviation of particle size distribution of 0.25

[0203] ·Binder: Tar pitch (10 parts by mass relative to 100 parts by mass of coke)

[0204] Aromatic compound: an additive containing methylnaphthalene (the total content of the aromatic compounds is 77% by mass or more, 3 parts by mass based on 100 parts by mass of coke)

[0205] The molded product obtained in Comparative Example 1 was evaluated in the same manner as in Example 1. Table 2 shows the results.

[0206] [Comparative Examples 2 and 3]

[0207] (Formation of Molded Article)

[0208] In Comparative Examples 2 and 3, calcined needle coke was used as an aggregate in the same manner as in Examples 2 to 8. Furthermore, the raw materials shown below were mixed while heating at 140°C in the proportions and conditions shown in Table 2 to prepare a mixture. Next, the obtained mixture was used to obtain graphite powder (negative electrode material for lithium ion secondary batteries) of Comparative Examples 2 and 3 by the same operation as in Comparative Example 1. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 2 respectively.

[0209] Aggregate: Needle coke with an average particle size of 10 μm and a standard deviation of particle size distribution of 0.24

[0210] ·Binder: Tar pitch (10 parts by mass relative to 100 parts by mass of coke)

[0211] Aromatic compound: an additive containing methylnaphthalene (the total content of the aromatic compounds is 77% by mass or more, 3 parts by mass or 7 parts by mass based on 100 parts by mass of coke)

[0212] [Comparative Example 4]

[0213] In Comparative Example 2, the graphite powder (negative electrode material for lithium ion secondary battery) of Comparative Example 4 was obtained in the same manner as in Comparative Example 2 except that the aromatic compound was not used, the amount of tar pitch was changed to the amount shown in Table 2, and the molding method was changed to extrusion molding. The density (g / cm 3 ), density of the burned product (g / cm 3 ) and the density of graphite (g / cm 3 ) are shown in Table 2 respectively.

[0214] The molded products obtained in Comparative Examples 2 to 4 were evaluated in the same manner as in Example 1. The results are shown in Table 2. "-" in the table means that there is no data.

[0215] [Table 1]

[0216]

[0217] [Table 2]

[0218]

[0219] In Examples 1 to 9, the bending test force (N) of the molded products tended to be superior to those of Comparative Examples 1 to 3, and the density of the graphitized products also tended to be small.

[0220] Furthermore, in Examples 1 to 9, the molded product was free of defects and large-scale molding was also possible.

[0221] In Examples 10 and 11 using extrusion molding, the density of the graphite tends to be smaller than that of Comparative Example 4. Furthermore, in Examples 10 and 11, large-scale molding can be performed.

[0222] All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described as being incorporated by reference.

Claims

1. A method for producing a negative electrode material for a lithium ion secondary battery, include: (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder, (b) forming the mixture to obtain a formed product, (c) a step of graphitizing the molded product to obtain a graphitized product, and (d) a step of crushing the graphitized material to obtain a crushed material; The adhesive includes a water-based adhesive containing a water-soluble or water-absorbent polymer compound.

2. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 1, in, In the step of obtaining a molded product, the mixture is molded to obtain a product with a density greater than or equal to 1.25 g / cm 3 The molded object.

3. A method for producing a negative electrode material for a lithium ion secondary battery, wherein include: (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder, (b) forming the mixture to obtain a density greater than or equal to 1.25 g / cm 3 The process of forming the product, (c) graphitizing the molded article to obtain a density less than or equal to 1.20 g / cm 3 The graphite process, and (d) A step of pulverizing the graphitized product to obtain a pulverized product.

4. A method for producing a negative electrode material for a lithium ion secondary battery, wherein include: (a) a step of obtaining a mixture comprising a graphitizable aggregate and a graphitizable binder, (b) forming the mixture by extrusion molding to obtain a molded product, (c) graphitizing the molded article to obtain a density less than or equal to 1.50 g / cm 3 The graphite process, and (d) A step of pulverizing the graphitized product to obtain a pulverized product.

5. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 3 or 4, in, The adhesive includes a water-based adhesive containing a water-soluble or water-absorbent polymer compound.

6. The method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1, 2 and 5, in, The water-soluble or water-absorbing polymer compound includes at least one selected from the group consisting of starch, amylose, amylopectin, polyacrylic acid, carboxymethyl cellulose, polyvinyl alcohol and water-soluble protein.

7. The method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1, 2, 5 and 6, in, The content of water in the mixture is 10% by mass to 50% by mass based on the total amount of the mixture.

8. The method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 7, in, The content of the binder in the mixture is 3% by mass to 30% by mass based on the total amount of the mixture.

9. The method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 8, in, The aggregate comprises calcined coke.

10. The method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 9, in, The aggregate comprises green coke which has not been subjected to thermal treatment.

11. A method for manufacturing a lithium ion secondary battery, comprising: include: A step of producing a negative electrode material for a lithium ion secondary battery by the method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 10, and A step of manufacturing a negative electrode using the negative electrode material for a lithium ion secondary battery.